Refleksi Sikap Denial dalam Kisah Nabi Yunus (Analisis Semiotika Roland Barthes Q.S. al-Anbiya’[21]: 87) - Pratama, Aziz Bashor (Journal of Arabic Language and Literature (ALLAIS), 2023)
Denial is implicitly alluded to in Q.S. al-Anbiya [21]: 87 which tells the story of the escape of Prophet Yunus from the conditions of his people. This study aims to identify the denial attitude contained in the verse, based on the argument that the Qur'anic text has implicit meanings that are relevant to the current context. The method applied in this research is descriptive-analytical by using Roland Barthes' semiotic approach to analyze the significance of the meaning of the Qur'anic text. The approach analyzes denotative and connotative meanings to bring out the mythology contained in the story of Prophet Yunus. This paper asks two questions: first, how is Roland Barthes' semiotic analysis of Q.S. al-Anbiya' [21]: 87? Second, how does the concept of denial reflect on the storyline of Prophet Yunus? This article concludes that denotatively Q.S. al-Anbiya' [21]: 87 shows the attitude of Prophet Yunus who left his people in a state of anger and prejudice against Allah SWT. The statement is in line with the concept of denial, which connotes the psychological condition of Prophet Yunus who was filled with feelings of disappointment with reality. He decided to deny by abandoning the responsibility given by Allah as a form of self-defense and protest against reality. The wisdom contained in Q.S. al-Anbiya' [21]: 87 is the prohibition of Allah Swt to His servants to be denial in dealing with problems and responsibilities.